2001
DOI: 10.1034/j.1600-0625.2001.010002100.x
|View full text |Cite
|
Sign up to set email alerts
|

Lectin and proteoglycan histochemistry of Merkel cell carcinomas

Abstract: Changes in carbohydrate residue expression and in proteoglycan distribution occur during different stages of tumor development and progression. However, few data concerning carbohydrate residue analysis as performed by lectin histochemistry and proteoglycan distribution of Merkel cell carcinoma, a rare malignant tumor of the skin, have been reported. Hence, lectin- and proteoglycan immunohistochemistry was performed on paraffin wax material of 9 cases of Merkel cell carcinomas characterized by cytokeratin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 44 publications
0
8
0
1
Order By: Relevance
“…20 A third and increasingly popular hypothesis is that MCCs originate from epidermal stem cells, with the capacity to differentiate into both neuroendocrine and epidermoid lineages. 22 This hypothesis may explain case reports of intraepidermal MCCs (MCC in situ), MCCs showing squamous metaplasia, and mixed MCCs and squamous cell carcinomas. 23,24 In our department, we have recently seen a primary cutaneous neuroendocrine carcinoma that showed this dual differentiation (Fig.…”
Section: Shared Ultrastructural Features and Immunocytochemical Markementioning
confidence: 90%
“…20 A third and increasingly popular hypothesis is that MCCs originate from epidermal stem cells, with the capacity to differentiate into both neuroendocrine and epidermoid lineages. 22 This hypothesis may explain case reports of intraepidermal MCCs (MCC in situ), MCCs showing squamous metaplasia, and mixed MCCs and squamous cell carcinomas. 23,24 In our department, we have recently seen a primary cutaneous neuroendocrine carcinoma that showed this dual differentiation (Fig.…”
Section: Shared Ultrastructural Features and Immunocytochemical Markementioning
confidence: 90%
“…The lectin-binding pattern of tumor cells varies among lectins with different sugar-binding specificities, while it is remarkably similar among tumors within a given nominal sugar specificity. Sames et al (2001) studied the reactions of Merkel cell skin carcinomas to lectins and observed that the most intense reaction was achieved using Con A (mannose/glucose-specific), followed by LCA with the same specificity, and the N -acetylglucosamine-specific lectins (WGA, UDA, CMA), while no fucose-binding sites were detected (UEA-I). In addition, galNAc residues were only occasionally detected.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…[56] Other legume lectins also have antiproliferative and anticancer properties such as concanavalin A, a lectin from Jack bean seed. [57] Several studies have suggested the cytotoxicity or tumor inhibition mechanisms of lectins to various tumor cell lines such as skin,[58] liver, bile duct, and bone cell lines. [59]…”
Section: Phytochemical Substances Act As Anticancer Activitymentioning
confidence: 99%